Efficacy Assessment of Ultrasound Guided Lauromacrogol Injection for Ablation of Benign Cystic and Predominantly Cystic Thyroid Nodules - Dong, Yijie; Zhou, Jianqiao; Liu, Zhenhua; Luo, Ting; Zhan, Weiwei (Frontiers in Pharmacology, 2019)
Background: To assess the efficacy and safeness of ultrasound guided lauromacrogol injection for ablation of benign cystic and predominantly cystic thyroid nodules. Methods: From July 2016 to July 2018, 102 patients with 107 nodules were treated with ultrasound guided lauromacrogol injection for ablation and 43 nodules completed at least 12 months follow-up. Nodules sonographic characteristics, volume changes before and after USG-LIA, and comlications were evaluated. Results: Mean nodule volume decreased from 17.27±20.51ml to 5.35±14.68ml (P<0.05), and the overall resolution rate (volume reduction rate>50%) was 91.67% in purely cysts and 75.90% in predominantly cystic nodules at last follow-up. Within 6 months after treatment, the volume of the target nodule at each follow-up was smaller than the previous one (P<0.001 for all). However, there was no significant difference of volume change between 6th month and 12th month. No severe complications occurred in this study. Conclusions: Ultrasound guided lauromacrogol injection for ablation is an effective and safe treatment modality in both purely cystic and predominantly cystic thyroid nodules.